ENTREPRENEURIAL OPPORTUNITIES: BUSINESS REALITIES FOR STUDENTS IN THE MIDST OF CHANGES IN ASN TEACHER RECRUITMENT REGULATIONS - Gunada, I Wayan Agus; Sutajaya, I Made; Sudiarta, I Gst. Putu (Guna Sewaka, 2023)
This article aims to explain the importance of education study program students and to see entrepreneurial opportunities amid changes in teacher recruitment regulations with ASN status. It is undeniable that the main hope for students of the education study program when they finish, can compete and graduate to become PNS or PPPK teachers, but amid changes in regulations related to recruitment, this hope may or may not be realized, so awareness is needed to be able to see entrepreneurial opportunities in addition to still trying to prepare abilities, towards competition in the recruitment process. The study uses qualitative research with a literature study approach. Based on the analysis results, it can be explained that IAHN Gde Pudja Mataram has three educational study programs: the Hindu Religious Education Study Program, Early Childhood Education, and Hindu Religious Arts and Culture Education. The three study programs emphasize the profile of graduates as professional educators and the profile to become entrepreneurs. Entrepreneurial opportunities that can be taken certainly adjust to the science of the study program; for example, the PAUD study program forms a literacy and counting course business, and the Hindu religious education study program can open a business for making and selling upakara tools. The art education study program takes business opportunities such as opening art courses, makeup artists, etc. The results of this study can become a reference library for relevant research in the future, and the information contained in this study can open and strengthen insights about the importance of entrepreneurship for students of education study programs